ANALISIS WACANA KRITIS TEUN A. VAN DIJK TERHADAP TEKS BERITA PEMBERHENTIAN GURU HONORER TAHUN 2026 PADA FRAMING MEDIA DARING NEWS.FIN.CO.ID DAN UNEWS.ID - Miftahul Husna Sirait; Karimaliana Karimaliana (STKIP Pesisir Selatan, 2026)
This study aims to analyze the discourse construction of news reporting regarding the dismissal of honorary teachers in 2026 on the online media News.fin.co.id and Unews.id using Teun A. Van Dijk’s Critical Discourse Analysis approach. This research employed a descriptive qualitative method focusing on the analysis of macrostructure, superstructure, and microstructure of the texts, supported by social cognition and social context analysis. The research data consisted of online news texts related to the dismissal of honorary teachers in 2026 published by both media outlets. Data collection techniques were conducted through documentation and text observation using purposive sampling, while data analysis was carried out through data reduction, data presentation, and conclusion drawing based on Van Dijk’s model. The results showed differences in framing between the two media in representing the policy of honorary teacher dismissal. News.fin.co.id emphasized the government’s perspective through aspects of regulation and bureaucratic reform, while Unews.id highlighted the social impacts and concerns of honorary teachers. These differences were reflected in news themes, information organization, diction selection, use of sources, and rhetorical strategies in shaping public opinion on contemporary educational issues.